هجاء الكتابة العربية في تراث ابن هشام الأنصاري (ت761هـ): " جمعًا ودراسة " 1444هـ ـ 2023م - د. الفضل إبراهيم الصادق علي (White Nile Journal for Studies and Research, 2023)
The study dealt with the topic: writing spelling in the legacy of Ibn Hisham Al-Ansari, and its importance lies in the fact that it highlights the images of drawing Arabic letters, and distinguishing between them because of the orthographic drawing of distinction in distinguishing the semantic, and defining the difference between spelling, drawing and spelling, and clarifying the drawing, and the forms and forms of Arabic. In this study, the researcher used the descriptive and inductive method, as he described the image by tracking it. The study reached results, the most important of which are: that the difference in the drawing is due in its entirety to phonetic harmony and mitigation, such as increasing the thousand after the ( waw gamaa) in the proverb (they said) and deleting it from the word sealed with waw is the lam of the word as in (nargo). And that the change of the graphic is due to the frequent use - sometimes - as in (Dawood and Taus), and the reduction - at another time - as in (Amen and Pir). As for the ya’, it is from the middle of the tongue, so it is softer in pronouncing it. The study recommends trying to develop an international drawing that combines different drawing images. A desire to link the rules of drawing among the ancients and the modern, and the extent of the existence of a relationship between forms of writing and semantics, with the aim of facilitating and facilitating communication between people.